Pengaruh Iklan dan Citra Merek terhadap Keputusan Pembelian Produk Indihome di Kabupaten Tabanan - Kusuma Dewi, Ni Made Megi (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study was conducted with the aim of understanding the impact of advertising and brand image on the purchase decision of Indihome products at Tabanan Regency. The object of this study includes all users of Indihome’s products and services, ie 11,709 customers in 2019-2021. The sample size is 100 people. In this study, we use Slovin’s formula. The data for this study were obtained through a questionnaire distribution, which was then analyzed using a variety of linear regression analysis techniques with the aim of determining the quantitative effect of a change (variable X). to other events (variable Y). Based on the research results, it can be seen that:(1) Advertising has a significant positive impact on product purchase decisions. This is shown by the value = 6,284 and (2) Brand image has a significant positive impact on product purchase decision. This is represented by the value = 5.919. (3) Advertising and branding simultaneously have a significant positive impact on product purchase decisions. This is represented by a value of 3.90 and a Fcount of 107,381. The level of influence of independent variables on product purchase decision is 68.2%. Suggestions for this study, in the coming time, the company needs to improve the quality of advertising for Indihome products, prepare the most attractive ads possible for customers to pay attention to when viewing.